2020
DOI: 10.3390/ijms21134662
|View full text |Cite
|
Sign up to set email alerts
|

Putative Roles for Peptidylarginine Deiminases in COVID-19

Abstract: Peptidylarginine deiminases (PADs) are a family of calcium-regulated enzymes that are phylogenetically conserved and cause post-translational deimination/citrullination, contributing to protein moonlighting in health and disease. PADs are implicated in a range of inflammatory and autoimmune conditions, in the regulation of extracellular vesicle (EV) release, and their roles in infection and immunomodulation are known to some extent, including in viral infections. In the current study we describe putati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 143 publications
(224 reference statements)
1
31
0
Order By: Relevance
“…The efficacy of ruxolitinib in calming the cytokine storm has been thoroughly investigated in animal models of HLS [ [118] , [119] , [120] , [121] , [122] , [123] ], showing that the mechanisms of action involve inhibition of among others CD8 + T cells and important inflammatory cytokines, including IFN gamma [ [148] , [149] , [150] , [151] , [152] ], being of utmost importance for the development of HLS [ 122 , 123 ]. Most lately, NETosis has attracted great interest in the pathogenesis of organ damage in COVID-19 afflicted patients [ [95] , [96] , [97] , [98] , [99] , [100] , [101] ], with NETs contributing both to ARDS and immunothrombosis in COVID-19 [ 101 ]. Accordingly, it has been argued that NETs might be a potential target in COVID-19 [ 95 ].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficacy of ruxolitinib in calming the cytokine storm has been thoroughly investigated in animal models of HLS [ [118] , [119] , [120] , [121] , [122] , [123] ], showing that the mechanisms of action involve inhibition of among others CD8 + T cells and important inflammatory cytokines, including IFN gamma [ [148] , [149] , [150] , [151] , [152] ], being of utmost importance for the development of HLS [ 122 , 123 ]. Most lately, NETosis has attracted great interest in the pathogenesis of organ damage in COVID-19 afflicted patients [ [95] , [96] , [97] , [98] , [99] , [100] , [101] ], with NETs contributing both to ARDS and immunothrombosis in COVID-19 [ 101 ]. Accordingly, it has been argued that NETs might be a potential target in COVID-19 [ 95 ].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…8. As alluded to above, most recent studies have shown that NETosis is deeply involved in thrombogenesis and organ damage in COVID-19 afflicted patients [ [95] , [96] , [97] , [98] , [99] , [100] , [101] ]. Ruxolitinib inhibits NET formation in patients with MPN [ 104 ] and may likely do so in patients with COVID-19 as well.…”
Section: Rationale For Treatment Of Covid-19 Patients With a Jak1/2 Imentioning
confidence: 99%
See 1 more Smart Citation
“…An in silico analysis of SARS-CoV-2-infected lung tissues and cell lines has identified that SARS-CoV-2-infection modulates the expression of PADs, predominantly PAD-2 and PAD-4, with link to inflammatory pathways. 33 Other studies have lent strong support to this notion by demonstrating that SARS-CoV-2 leads to activation of neutrophils and triggers the release of neutrophil extracellular traps (NETs) in the circulation 34,35 and organ tissues. 34 NETs are extracellular webs of DNA, proteins and histones, and their release was found to be dependent on ACE2, serine protease, virus replication, and PAD-4 activation.…”
Section: Deimination/citrullinationmentioning
confidence: 97%
“…Recent studies have proposed a role for posttranslational deimination by peptidylarginine deiminases (PADs) in SARS-CoV-2-infection. 3335 Deimination converts arginine residue in a protein into citrulline, and allows the modified protein to carry out multifaceted functions, a phenomenon termed “protein moonlighting.” There are five PADs in humans, with different tissue expressions and deimination activities, and they are involved in multiple diseases, including autoimmune diseases and viral infections. An in silico analysis of SARS-CoV-2-infected lung tissues and cell lines has identified that SARS-CoV-2-infection modulates the expression of PADs, predominantly PAD-2 and PAD-4, with link to inflammatory pathways.…”
Section: Sars-cov-2 Infection-induced Ptms Other Than Phosphorylationmentioning
confidence: 99%